2018
DOI: 10.1002/cam4.1739
|View full text |Cite
|
Sign up to set email alerts
|

Radiological characteristics and predisposing factors of venous tumor thrombus in pelvic osteosarcoma: A mono‐institutional retrospective study of 115 cases

Abstract: BackgroundVenous tumor thrombus (VTT) in pelvic osteosarcoma has been regarded as a rare oncological condition and few literatures investigated this issue.MethodsWe retrospectively reviewed 115 cases of pelvic osteosarcoma treated in our center from 2006 to 2016. Diagnosis of VTTs was made based on histo‐pathological findings. We summarized the radiological manifestations of VTTs on CT, MRI, and PET/CT. We also compared the demographical, oncological, and radiological data between cases with or without VTTs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(107 reference statements)
2
7
0
Order By: Relevance
“…In the above study, although the multi-factor regression analysis showed that age and Pfirrmann's classification of intervertebral disc were independent factors, it also had certain influence on the curative effect, among them, the age increased, the water content of nucleus pulposus, the elasticity of intervertebral disc and the anti-load ability decreased gradually, at the same time, the elderly patients had poor physical fitness and their organ function and osteoporosis were poor, which brought some difficulties to the surgery, while the Pfirrmann's classification of disc degeneration reflects the degree of disc degeneration, the greater the grade, the greater the degree of disc degeneration and the worse the effect of LDH. This is similar to the results of the study by Haijie et al [15] .…”
Section: Resultssupporting
confidence: 93%
“…In the above study, although the multi-factor regression analysis showed that age and Pfirrmann's classification of intervertebral disc were independent factors, it also had certain influence on the curative effect, among them, the age increased, the water content of nucleus pulposus, the elasticity of intervertebral disc and the anti-load ability decreased gradually, at the same time, the elderly patients had poor physical fitness and their organ function and osteoporosis were poor, which brought some difficulties to the surgery, while the Pfirrmann's classification of disc degeneration reflects the degree of disc degeneration, the greater the grade, the greater the degree of disc degeneration and the worse the effect of LDH. This is similar to the results of the study by Haijie et al [15] .…”
Section: Resultssupporting
confidence: 93%
“…VTT was previously reported to predict a worse outcome for a pelvic osteosarcoma 17,18 . In our study, it was associated with shorter overall survival (21.5 versus 54.0 months), recurrence-free survival (18.6 versus 32.4 months), and metastasisfree survival (11.2 versus 41.0 months) in patients with localized disease.…”
Section: Prognosis Of Pelvic Sarcomas With Vtt At Presentationmentioning
confidence: 94%
“…For the cases of VTT without pathological confirmation, the diagnosis was based on published radiographic criteria: (1) absence of a flowing void effect within the vein on T2-weighted MRI and a filling defect within the vein on enhanced CT/MRI; (2) calcification, or fillings within the vein with the same imaging characteristics as the primary tumor; (3) dilated caliber of the vein; (4) "thread and streaks" sign, or streak-like enhancement within the vein; or (5) high metabolic activity within the vein on an 18 FDG (fluorodeoxyglucose) PET/CTscan. The presentation of (2) through ( 5) above was helpful for differential diagnosis from benign thrombus (see Appendix Table S1) 17,18 . We proposed a classification system (the Peking University People's Hospital [PKUPH] system) for VTT in pelvic sarcomas (Fig.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard treatment for OS is still surgery combined with chemotherapy and neoadjuvant chemotherapy ( 7 ). Furthermore, the clinical outcomes of OS and ES in the pelvis and sacrum have been shown to be inferior to those in other sites due to the larger sizes of the lesions when found and the difficulty in obtaining a wide surgical resection margin ( 5 , 8 , 9 ). Clinically, an auxiliary diagnostic tool is needed to improve the accuracy of distinguishing OS from ES to promptly formulate individualized treatment plans ( 10 ).…”
Section: Introductionmentioning
confidence: 99%